One new trematode species Metorchis kimbandensis sp.nov. (Trematoda: Opisthorchiidae) parasiting in the catfish (Parasilurus asotus) from Vietnam - Ha, Nguyen Van (Academia Journal of Biology, 2014)
One new trematode species Metorchis kimbandensis sp.nov. (Trematoda: Opisthorchiidae) parasiting in the catfish (Parasilurus asotus) from Vietnam